1993
DOI: 10.1136/jmg.30.6.454
|View full text |Cite
|
Sign up to set email alerts
|

Population studies of the fragile X: a molecular approach.

Abstract: The fragile X mutation can now be recognised by a variety of molecular techniques. We report a pilot screening survey of a population of children with mental impairment in which we used Southern blotting methods to detect the fragile X mutation, augmented by cytogenetic studies on children whose phenotype suggested a possible chromosome abnormality. There were 873 children with special educational needs in our survey and 310 fulfilled our criteria for testing. A sample was obtained from 254, of whom four were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 11 publications
8
49
3
Order By: Relevance
“…In agreement with other studies, [21][22][23][24][25][26][27][28][29] A-2 and D-6 were also highly prevalent in our sample (38% of patients), supporting the contention that these two haplotypes are present on ancestral European fragile X founder chromosomes. 28,29 The presence of haplotypes C-2 and C-5 in 16 (38%) fragile X chromosomes, suggests the existence of specific founder mutations in Portuguese patients, since no similar findings have been observed in other populations.…”
Section: Discussionsupporting
confidence: 80%
“…In agreement with other studies, [21][22][23][24][25][26][27][28][29] A-2 and D-6 were also highly prevalent in our sample (38% of patients), supporting the contention that these two haplotypes are present on ancestral European fragile X founder chromosomes. 28,29 The presence of haplotypes C-2 and C-5 in 16 (38%) fragile X chromosomes, suggests the existence of specific founder mutations in Portuguese patients, since no similar findings have been observed in other populations.…”
Section: Discussionsupporting
confidence: 80%
“…Our inference of disparate rates of normal-topremutation events is consistent with early suggestions of chromosomal haplotype effects on FMR1 stability (Richards et al, 1992;Chakravarti, 1992;Jacobs et al, 1993), and with subsequent analyses of the substructure of CGG repeats, which revealed greater stability for alleles with AGG interruptions (Eichler et al, 1995;Kunst and Warren, 1994). Significant differences in the abundance and locations of stabilizing AGG interruptions have been reported for alleles sampled in Japan as compared to alleles sampled in non-Asian populations (Hirst et al, 1997).…”
Section: Resultssupporting
confidence: 73%
“…2). This finding suggests that different rates of normal-to-premutation, as proposed under the founder-haplotype hypothesis (Richards et al, 1992;Chakravarti, 1992;Jacobs et al, 1993), could be sufficient to yield substantial variation in carrier frequencies. This founder-haplotype hypothesis is also consistent with earlier reports that Asian and non-Asian populations may differ in their distributions of FMR1 alleles with various numbers and positions of AGG repeats within the CGGrepeat region (see, for example Hirst et al, 1997).…”
Section: Resultsmentioning
confidence: 77%
“…As a consequence, essentially all estimates to date have targeted populations with special education needs or mental retardation, with subsequent extrapolation to the general population. Earlier estimates of one full-mutation allele in 5000 to 9000 individuals [13][14][15] are likely to be too low, because those estimates did not fully account for fragile X children without mental retardation. More recent estimates are generally higher, from one in 2500 to 5000 for the larger studies of special education needs children 6,16,17,18 -20 ; however, as for premutation alleles, there have been no large-scale unbiased (eg, newborn) screens for full-mutation FMR1 alleles in the general population, due in part to the absence of an effective screening tool.…”
mentioning
confidence: 99%